2004
DOI: 10.1073/pnas.0400805101
|View full text |Cite
|
Sign up to set email alerts
|

Functional association between Wwox tumor suppressor protein and p73, a p53 homolog

Abstract: The WWOX gene is a recently cloned tumor suppressor gene that spans the FRA16D fragile region. Wwox protein contains two WW domains that are generally known to mediate protein-protein interaction. Here we show that Wwox physically interacts via its first WW domain with the p53 homolog, p73. The tyrosine kinase, Src, phosphorylates Wwox at tyrosine 33 in the first WW domain and enhances its binding to p73. Our results further demonstrate that Wwox expression triggers redistribution of nuclear p73 to the cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
275
3
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(294 citation statements)
references
References 21 publications
12
275
3
4
Order By: Relevance
“…Our observation that the inhibition of endogenous WWOX expression enhances the effect of Wnt-3a on b-catenin stability supports this hypothesis. WWOX has earlier been shown to associate with p73, AP2-g, c-Jun and ErbB-4 in the cytoplasm and prevents their translocation into the nucleus, thereby inhibiting their transcriptional activity (Aqeilan et al, 2004a(Aqeilan et al, , 2004bGaudio et al, 2006). The sequestration of protein in the perinuclear compartment by WWOX seems, therefore, to be an important mechanism antagonizing the function of various proteins involved in the modulation of transcription, including Dvl proteins, in this study.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Our observation that the inhibition of endogenous WWOX expression enhances the effect of Wnt-3a on b-catenin stability supports this hypothesis. WWOX has earlier been shown to associate with p73, AP2-g, c-Jun and ErbB-4 in the cytoplasm and prevents their translocation into the nucleus, thereby inhibiting their transcriptional activity (Aqeilan et al, 2004a(Aqeilan et al, , 2004bGaudio et al, 2006). The sequestration of protein in the perinuclear compartment by WWOX seems, therefore, to be an important mechanism antagonizing the function of various proteins involved in the modulation of transcription, including Dvl proteins, in this study.…”
Section: Discussionsupporting
confidence: 51%
“…These results suggest strongly that WWOX does not inhibit the Wnt/ b-catenin pathway by disrupting the interaction of Dvl-2 with the b-catenin-degradation complex. (Aqeilan et al, 2004a(Aqeilan et al, , 2004bGaudio et al, 2006). These results and ours therefore raise the possibility that WWOX would inhibit the transcriptional activity of the Wnt/b-catenin signaling pathway by preventing the entry of Dvl into the nucleus.…”
Section: Binding Domainssupporting
confidence: 60%
“…p73 localizes to mitochondria AE Sayan et al through the PPXY motif located at the p73 C terminus (amino acids between 482 and 488; Aqeilan et al, 2004). Although we could not map the internal cleavage sites in p73, all detected p73 fragments (F1, F2 and F3) should contain the PPXY motif as they are detected by p73SAM antibody that is raised against amino-acid residues 487-554 of TAp73a.…”
Section: Discussionmentioning
confidence: 72%
“…Although we could not map the internal cleavage sites in p73, all detected p73 fragments (F1, F2 and F3) should contain the PPXY motif as they are detected by p73SAM antibody that is raised against amino-acid residues 487-554 of TAp73a. This interaction induces the shuttle of p73 from nucleus to cytoplasm in an Srcdependent manner and increases the apoptotic activity of Wwox protein (Aqeilan et al, 2004). Therefore, a further possibility is that p73 or p73 cleavage fragments migrate to the cytoplasm/mitochondria following interaction with WW domain containing proteins.…”
Section: Discussionmentioning
confidence: 99%
“…4 WWOX is known to participate in several physiological functions through interaction with several regulators, such as Dvl proteins for the regulation of Wnt-catenin pathway, 5 JNK and c-Jun for JNK signaling, 4,6 RUNX2 for osteoblast differentiation 7 , and p53/p73 for apoptosis. 8,9 Previous report showed that WWOX is a novel regulator in extracellular signal-regulated kinase (ERK) signaling through interaction with MEK2. 10 ERK signaling is important for the control of cell proliferation, migration, cell division, and differentiation.…”
mentioning
confidence: 99%